Influência do consumo proteico, da prática de atividade física, do controle metabólico, do estágio de maturação sexual e do IMC no percentual de gordura corporal de adolescentes fenilcetonúricos - Giovanna Caliman Camatta (2017)
Overweight and obesity have been increasing significantly in our society, including in patients with phenylketonuria (PKU). It is known that dietary intake and physical activity level are factors that contribute to determination of body composition. Nevertheless, an investigation of the amount of physical activity performed by PKU patients is absent in the literature. This fact along with the importance of protein consumption levels for treatment success motivates an analysis of the influence of these aspects on body fat of PKU patients. The present study aims to evaluate body fat percentage of PKU adolescents and relate it to protein intake, physical activity level, body mass index (BMI), sexual maturity stage and blood concentration of phenylalanine (phe). The analysis is cross-sectional and the sample is composed of 94 adolescents, aged 10 to incomplete 20 years, with early diagnosis of PKU and currently under treatment in the Special Service of Genetics of Hospital das Clínicas of Federal University of Minas Gerais. In order to evaluate the nutritional status of patients, bioimpedance, weight, height and BMI measurements were carried out. Questionnaires were applied to quantify protein intake (food frequency questionnnaire (FFQ) and food records) and to assess the physical activity level (Physical Activity Questionnaire for Older Children (PAQ-C), while the stage of sexual maturation was determined based on Tanner's criteria. The average phe blood level in the previous year was taken as a proxy for disease control. The statistical analysis comprised Spearman's rank correlation coefficient test, Student's t-test and Mann-Whitney U test, as well as multivariate regression analysis. The results of the latter reveal that overweight, obesity, female gender and dietary protein consumption percentage account for 94.1% of the body fat percentage of patients. BMI and body fat percentage showed to be strongly correlated in girls (r = 0.649, p < 0.001) and moderately correlated in boys (r = 0.364, p < 0.007). Overweight prevalence in the sample was 19.1%, while sedentary behavior was observed in 96.7% of patients. Females have a lower level of physical activity (p = 0,008). No gender distinction was found for BMI values, protein consumption and metabolic control. A little more than half of the sample (53.2%) showed good treatment adherence, but no correlation was found between this variable and body fat percentage (p = 0.706). There was also no correlation between daily average protein intake and phe blood level control (r = -0.124, p = 0.234). The results lead to the conclusion that, similarly to what is observed in the general population, being female and presenting high BMI values are important factors associated to body fat percentage in PKU adolescents. On the other hand, the challenges of quantifying food consumption, as well as the weak statistical results, do not allow the conclusion that protein intake has an influence on body fat levels.